KETERAMPILAN DASAR MENGAJAR GURU DALAM PEMBELAJARAN TAJWID DI RA MAMBAUL ULUM BATA-BATA - Latifatul Mahbubah; Ahmad Faisol Amin; Abd. Aziz; Abdillah Fahrul Rozi; Ahmad Badriyadi (Tarbawi, 2022)
Mastering teaching skills is crucial for the effectiveness of the learning process. This study is focused on the analysis of basic teaching skills among teachers who teach Tajweed at RA Mambaul Ulum Bata-Bata. The method used in this research is qualitative descriptive. Data was collected through structured interviews, observations, and document collection. The findings indicate an adequate performance of the teachers in various teaching skills such as opening and closing teaching sessions, explanatory ability, the capacity to pose questions, expertise in providing positive feedback verbally and nonverbally, as well as proficiency in guiding discussions. Other teaching skills were also categorized as good.